Beckman Microzone Electrophoresis Cell - Hesketh, Dean D. (1964)
Electrophoresis uses an electric field to separate particles in a medium (like a gel) based on their size, charge, or a binding affinity.
Keywords: Electrophoresis; Scientific apparatus and instruments; Electrophoresis--Equipment and supplies; Beckman Instruments, Inc.